2002
DOI: 10.4161/cbt.59
|View full text |Cite
|
Sign up to set email alerts
|

A Nucleotide Excision Repair Master-Switch: p53 Regulated Coordinate Introduction of Global Genomic Repair Genes

Abstract: © 2 0 0 2 L a n d e s B i o s c i e n c e . N o t f o r d i s t r i b u t i o n .[Cancer Biology & Research Article A Nucleotide Excision Repair Master-Switch: p53 Regulated Coordinate Induction of Global Genomic Repair Genes ABSTRACTThe tumor suppressor gene p53 is mutated in many human cancers. One of its major roles is as a transcription factor, and its many effector genes control key cellular processes including cell cycle checkpoints and apoptosis. An important role in DNA repair is also emerging for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 30 publications
4
47
1
Order By: Relevance
“…28 -30 It has been suggested that p53 play a role in regulating NER, especially the GGR subpathway. [31][32][33][34][35][36] As shown in our experiment, a heterozygous loss of p53 appears to act synergistically to a NER defect in tongue tumor induction. The bulky DNA lesions elicited by 4NQO are known to substrate for GGR and 4NQO-DNA damage per se provokes up-regulation of p53.…”
Section: Discussionmentioning
confidence: 79%
“…28 -30 It has been suggested that p53 play a role in regulating NER, especially the GGR subpathway. [31][32][33][34][35][36] As shown in our experiment, a heterozygous loss of p53 appears to act synergistically to a NER defect in tongue tumor induction. The bulky DNA lesions elicited by 4NQO are known to substrate for GGR and 4NQO-DNA damage per se provokes up-regulation of p53.…”
Section: Discussionmentioning
confidence: 79%
“…Several mechanisms have been suggested for the observed enhancement of DNA repair by p53. These include transcriptional upregulation of DNA repair factors such as DDB2 and XPC (Adimoolam and Ford, 2002;Amundson et al, 2002;Tan and Chu, 2002;Fitch et al, 2003), recruitment of repair factors to sites of DNA damage through physical interaction with p53 (Wang et al, 2003) and the ability of p53 to function as a chromatin accessibility factor to allow access of repair factors to sites of damage (Rubbi and Milner, 2003). Given that E2F1 can upregulate the expression of a number of DNA repair genes (Wang et al, 1999;Polager et al, 2002;Ren et al, 2002) and that E2F1 physically associates with several DNA repair factors (Hayes et al, 1998;Maser et al, 2001;Liu et al, 2003), it is quite possible that like p53, the antiapoptotic effect of E2F1 is related to a stimulation of DNA repair.…”
Section: E2f1 Regulation Of Apoptosismentioning
confidence: 99%
“…In addition to regulation of cell cycle checkpoints that arrest cells, giving them time to repair damage, p53 also activates genes that are in some way more directly involved in DNA repair responses (Figure 3). These include p53R2, a ribonucleotide reductase involved in replenishing nucleotide pools, and the xeroderma pigmentosum genes XPC and XPE Amundson et al, 2002;Takimoto et al, 2002a;Tan and Chu, 2002). XPE encodes a DNA damagebinding protein DDB2, also known as p48, which is part of a herterodimer with p125 and involved in DNA damage recognition and binding following ultraviolet light damage.…”
Section: Cellular and Tissue-specific Effects Of P53mentioning
confidence: 99%
“…Further understanding of the control of subcellular localization of p53 has emerged from a number of regulators such as MDM2, ARF, and Parc (Kastan and Zambetti, 2003;Lowe and Sherr, 2003;Michael and Oren, 2003;Nikolaev et al, 2003). A greater appreciation of the role of p53 in DNA repair has been realized with the identification of direct targets for transcriptional activation including p53R2, the XPE gene product DDB2 or p48, and XPC, genes whose proteins are directly involved in DNA repair processes Amundson et al, 2002;Takimoto et al, 2002a;Tan and Chu, 2002).…”
Section: Introductionmentioning
confidence: 99%